Synthesis of N –sulfamethoxazolederivative imide on polymeric chain (Baghdad Science Journal, 2014)
The present work involved synthesis of several new N-Sulfamethoxazol derivatives imide on Polymeric chain by two steps. The first stip involved preparation of N- (sub.orunsub benzoyl and sub unsub acetyl) amidyl sub sulfamethoxazole (1-5) by condensation of sulfamethoxazole drug with many substituted acid chloride, then the second step include, preparation new five N-(acrly-N–sub or unsub benzoyl) imidyl substituted sulfamethoxazol(6-10) by reaction of poly acryloyl chloride with the prepared compound (1-5) in first stepin asuitable solvent in the presenceamount triethylamine (Et3N) with heating. The structure confirmations of all polymers wereconfirmed using FT-IR,1H-NMR,13C-NMR and UV spectroscopy. Other physical properties including softeningpoint's, melting point, and solubility of the polymers were also measured.